The complementarity between trust and contract enforcement - Björn Bartling; Ernst Fehr; David Huffman; Nick Netzer (University of Zurich, Department of Economics, 2024)
Agreements are rarely fully enforceable, exposing trading parties to some risk of exploitation. In such circumstances, trust-defined as the belief in the trustworthiness of others-seems important for realizing gains from trade. This paper explores an unstudied question: whether trust is a substitute for, or a complement to, the availability of contract enforcement opportunities. One intuition suggests that trust becomes more important when contract enforcement is weak, implying that they are substitutes. We show, however, that trust can be a complement, mattering more when contract enforcement is stronger. Our evidence comes from experiments that exogenously vary both trust and contract enforcement. We argue that the mechanism is equilibrium selection: richer opportunities for contract enforcement can lead to a wider set of equilibria. Trust can then become more important because it helps select between efficient and inefficient equilibria. We provide empirical evidence for this mechanism, and a corresponding theoretical framework. The complementarity of trust and strength of contract enforcement has important policy implications.
Keywords: C91; D02; D91; E02; 330; Trust; contract enforcement; complementarity; equilibrium selection; causal effect; screening; belief distortions; institutions